Monoamniotic Monochorionic Twins—Can They Be Delivered Safely Via Vaginal Route? [9]. (May 2016) - Khandelwal, Meena; Revanasiddappa, Vanitha B.; Moreno, Sindy C.; Simpkins, Gunda; Weiner, Stuart; Westover, Thomas
Abstract : INTRODUCTION: Current ACOG technical bulletin #144, 2014 states "Women with monoamniotic twin gestations should undergo cesarean delivery to avoid an umbilical cord complication of the nonpresenting twin at the time of the initial twin's delivery." To assess feasibility of vaginal delivery, we compared neonatal outcomes after attempted VD versus planned cesarean delivery (CD). METHODS: This retrospective cohort study from 2 tertiary-care centers, reviewed all viable MoMo twin pregnancies beyond 24 weeks gestation, delivered over last 15 years. Independent T test and Fisher exact test were used for statistical analysis. RESULTS: Of 29 women with MoMo twins, 15 underwent planned CD and 14 attempted VD. Of the 14 women who attempted VD: 6 underwent IOL; 10 successfully delivered both neonates vaginally with median interval of 3 minutes between the twins; 3 underwent CD for non-reassuring fetal tracing; 1 required CD for the 2nd twin. Despite similar GA at delivery (32.7 vs 33.3 weeks; P =.5) and fetal loss rate (2/15 vs 1/14; P =NS), incidence of intracranial hemorrhage was significantly lower in the vaginally delivered neonates (0 vs 8; P =.006); lower trends were also noted in neonatal length of stay (18 vs 25, P =.09) and respiratory complications. Entangled cords were noted in 28/29 pregnancies at birth. Women with prior CD more often chose repeat CD. Composite maternal outcomes were similar in the 2 groups. CONCLUSION/IMPLICATIONS: VD appears to be safe in appropriately identified MoMo twins. Current practice and recommendations are based on theoretical risks. This study, though small, provides valuable data on option of vaginal delivery for MoMo twins.